Toward marriage sustainability: Impacts of delayed marriages in Qatar - Noora Lari (14158824) (2022)
Qatar society demonstrates an interesting opportunity to examine the impacts of recent socioeconomic developments on family cohesion and marriage formation. This study describes individual-level factors (e.g., education, occupation) and societal-level factors (e.g., religion, culture, and norms) for marriages’ postponement among Qataris, which adversely impacts individuals, families, and entire society. Semi-structured interviews were conducted with male and female participants. The discussions addressed core aspects influencing marriage timing for men and women (e.g., marriage type, spousal selection, marriage costs and expenses, social bias and gender differentials at the household level). Policy instruments were suggested as follows: subsidizing the state-granted marriage fund on the country-level, and redefining gender roles within the family context. Other Information Published in: Cogent Social Sciences License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/23311886.2022.2083480